Dominance and Structural Variation in Deciduous Forests - George, M.; Varghese, G. (Indian Forester, 1985)
Structural formation of three deciduous forest vegetation communities were studied and profile diagrams were drawn and described. The communities grown at three different locations show differences in species composition, structure, growth parameters, species distribution etc. The area which receives an average annual rainfall of about 1500 mm to 2500 mm carries moist mixed deciduous forests where Terminalia tomentosa and Lagerstroemia microcarpa are the dominant trees, while areas where rainfall is about 750 to 1500 mm, dry deciduous forests with Tectona grandis and Anogeissus latifolia as dominant trees occur. Locations where the rainfall is less than 750 mm Anogeissus latifolia and Acacia chundra dominate.